The Maze Runner, the pandemic, and the Gospel. (May 2022) - Hamilton, Nick
The Maze Runner book series and movie trilogy is set in the future, when ecological disaster and a global pandemic strike. Many children and young adults are immune to the disease and are therefore quarantined, studied, and used to develop a cure for the "flare." This article examines some of the ethical frameworks experienced in the COVID-19 pandemic using the Maze Runner movies as illustrations. It also examines contemporary culture and proposes that a more robust gospel witness is needed to better deal with future global pandemics.